2021
DOI: 10.3389/fphys.2021.654755
|View full text |Cite
|
Sign up to set email alerts
|

An Endurance-Dominated Exercise Program Improves Maximum Oxygen Consumption, Ground Reaction Forces, and Muscle Activities in Patients With Moderate Diabetic Neuropathy

Abstract: BackgroundThe prevalence of diabetes worldwide is predicted to increase from 2.8% in 2000 to 4.4% in 2030. Diabetic neuropathy (DN) is associated with damage to nerve glial cells, their axons, and endothelial cells leading to impaired function and mobility.ObjectiveWe aimed to examine the effects of an endurance-dominated exercise program on maximum oxygen consumption (VO2max), ground reaction forces, and muscle activities during walking in patients with moderate DN.MethodsSixty male and female individuals age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…A higher CRF is associated with improved survival and decreased incidence of CVD and other comorbidities, including hypertension, diabetes, heart failure, and atrial fibrillation ( 54 ). A previous study has shown that brisk walking can assist to improve cardiopulmonary fitness by increasing blood circulation, oxygen intake, and heart rate ( 55 ). Identically, this literature review revealed that moderate-intensity brisk walking had a positive and significant effect on cardiorespiratory fitness for elderly women and a mixture of males and females, but limited evidence presented on males ( 21 , 22 , 24 , 26 , 27 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A higher CRF is associated with improved survival and decreased incidence of CVD and other comorbidities, including hypertension, diabetes, heart failure, and atrial fibrillation ( 54 ). A previous study has shown that brisk walking can assist to improve cardiopulmonary fitness by increasing blood circulation, oxygen intake, and heart rate ( 55 ). Identically, this literature review revealed that moderate-intensity brisk walking had a positive and significant effect on cardiorespiratory fitness for elderly women and a mixture of males and females, but limited evidence presented on males ( 21 , 22 , 24 , 26 , 27 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased serum FGF21 levels may predict the clinical response to aerobic exercise. Previous studies have demonstrated a significant improvement in neurological function, affecting both sensorimotor and autonomic components of the peripheral nervous system, in patients with DN during physical exercise programmes [ 2 , 36 ]. The mechanism of improvement of neuropathic symptoms and nerve function is thought to be related to improvement in endothelial dysfunction and reduction of inflammation in DN.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that physical activity may improve the neurological function and impaired nerve conduction in DN [ 2 ]. Physical activity and regular exercise are effective interventions to reduce the development and progression of diabetic neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic neuropathy (DN) with damage to glial neurons, their axons, and endothelial cells leads to impaired brain function (1). Insulin signaling in the brain regulates neuronal survival, synaptic plasticity, and cognitive and locomotor functions (2).…”
Section: Introductionmentioning
confidence: 99%